New species of Illiesonemoura and Nemoura (Plecoptera: Nemouridae) from Yunnan Province of southern China - Zhao, Meng-Yuan; Rehman, Abdur; Du, Yu-Zhou (Zootaxa, 2023)
Two new species of Nemouridae, Illiesonemoura qianae Du, Zhao, & Rehman sp. nov. and Nemoura longistyla Zhao, Rehman & Du sp. nov., are described and illustrated from Yunnan Province of southern China. The morphological characteristics of the new species are compared to related taxa and new images are also provided.